Penyelesaian Kredit Macet dengan Jaminan Hak Tanggungan pada PT Bank Perekonomian Rakyat Pulau Punjung - Irawan, Fira; Dilova, Gisha; Wulandari, Ratih Agustin (IAI Nasional Laa Roiba Bogor, 2024)
Providing credit does not always run smoothly, there are some loans that are bad because debtors do not carry out their obligations properly. If bad credit is not handled properly, it will have a bad impact on PT BPR Pulau Punjung because it will disrupt cash flow in and out. This research aims to find out: (1) What is the process of resolving bad credit with mortgage guarantees carried out by BPR Pulau Punjung? (2) What are the obstacles and constraints faced by BPR Pulau Punjung in resolving bad credit with collateral? (3) What efforts have been made by BPR Pulau Punjung to resolve the problems or obstacles that occur in bad credit with mortgage guarantees? This research method is empirical and includes descriptive research. The data source was obtained from interviews. The data collection techniques were literature study and field study. The results of this research are (1) The resolution of bad credit at PT BPR Pulau Punjung was carried out very well by making various efforts to save credit and in accordance with banking procedures. (2) constraints and obstacles faced by PT. Punjung Island BPR in resolving bad credit with mortgage guarantees is difficult to meet customers, bad customer character, economic factors, the credit given is not fully used for business, the debtor is not open to creditors, the debtor is negligent in the agreement, the condition of the debtor's family is not conducive. . (3) Efforts made by PT. Punjung Island BPR in resolving the problems and obstacles that occur in bad credit with collateral rights is applying the 5C 7P and 3R principles, and BPR proposes various efforts for bad credit which can still be saved by finding out the factors causing the bad credit by re-surveying and considering returned a request to save the bad credit. In conclusion, before executing the PT guarantee. BPR has made various efforts to save bad credit so that the debtor's credibility does not decline.